Ethiopia - A Qualitative Understanding of Local Traditional Knowledge and Medicinal Plant Use - World Bank (Washington, DC, 2012)
The fieldwork-based study aims to gain insight into the local distribution of traditional health knowledge and the uses of various medicinal plants among ordinary men and women in rural communities, who constitute the vast majority of Ethiopia's population. The overall aim of the research is to contribute to the growing body of literature and experience pertaining to the role of indigenous/traditional systems of knowledge in development. Underlying this objective is the fundamental premise that health constitutes the linchpin of the development process, viewed at once, both as the means as well as the end of development. The fieldwork was carried out with the participation of communities in the rural Bahir Dar Zuria district of Gojam (now part of the Amhara Regional State) located in the North Western Highlands of the country. A combination of research tools from various disciplines were employed. Gender considerations constituted an integral and cross-cutting aspect of the methodology, as important gender factors were expected to be involved, inter alia, in the distribution of traditional health knowledge and its inter-generational transmission.